2016
DOI: 10.1556/0806.44.2016.004
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance study and stable sources of maydis leaf blight(Cochliobolus heterostrophus)resistance in tropical maize germplasm

Abstract: Maydis leaf blight (MLB), a serious foliar fungal disease of maize, may cause up to 40% losses in yield. The present studies were undertaken to identify the stable sources of MLB resistance, its inheritance study, and testing of MLB resistance linked markers from diverse background in the Indian adapted tropical maize genotypes. A set of 112 inbred lines were screened under artificially created epiphytotics conditions at three hotspot locations. Analysis across multi-locations revealed significant effects of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…Estimates of means of the squares from effects found SCA values to be higher than the GCA ones (Table 1); it indicated that the gene actions and genetic structure of the evaluated hybrids favored manifestation of non-additive gene effects. Studies indicate that genetic resistance to southern corn leaf blight in Corn is predominantly determined by additive effect genes (Kumar et al, 2016;Li et al, 2018). However, the existence of non-additive effects on B. maydis control has also been reported in the literature (Carson et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Estimates of means of the squares from effects found SCA values to be higher than the GCA ones (Table 1); it indicated that the gene actions and genetic structure of the evaluated hybrids favored manifestation of non-additive gene effects. Studies indicate that genetic resistance to southern corn leaf blight in Corn is predominantly determined by additive effect genes (Kumar et al, 2016;Li et al, 2018). However, the existence of non-additive effects on B. maydis control has also been reported in the literature (Carson et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Seventeen newly developed QPM inbred lines were screened against maydis leaf blight and charcol rot by Kumar et al, (2013) Malik et al, 2015. Kumar et al, (2016 carried out inheritance study on 112 inbred maize lines and identified the stable source of MLB resistance, and MLB resistance linked markers from diverse background in the Indian adapted tropical maize genotypes.…”
Section: Resultsmentioning
confidence: 99%
“…However, in tropical regions of SSA, maize production is frequently affected by southern corn leaf blight (SCLB), a foliar disease caused by the fungus Bipolaris maydis (Y. Nisik. and C. Miyake) Shoemaker (teleomorph: Cochliobolus heterostrophus Drechsler) (Kumar et al 2016). The disease can be catastrophic such as during the infamous 1970-1971 epidemic in the US caused by Race T (Bhandari et al 2017;Tatum 1971;Ullstrup 1972).…”
Section: Introductionmentioning
confidence: 99%